Pengelolaan Materi Moderasi Beragama, Etika, dan Budaya dalam Pembelajaran Sastra Indonesia di Madrasah Aliyah - Nuryati Djihadah (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
This research aims to describe the concept of internalization of the values of religious moderation, ethics and culture in literary learning in Madrasah Aliyah. This research uses a qualitative approach with descriptive methods of analytics. Research data collection techniques use interviews, observations, and documentation. The study respondents were Indonesian language and literature teachers in Madrasah Aliyah Soebono Mantofani and Madrasah Aliyah Islamiyah Ciputat students of South Tangerang City of Banten province. The results of this study explain that the internalization of the values of religious moderation, ethics and culture can be developed through the management of literary learning in Madrasah Aliyah. Internalization of the values of religious moderation, ethics and culture is applied through learning management in the form of planning, organizing, implementing, and assessing or evaluating learning so as to form the attitude of religious moderation of students.